2021
DOI: 10.1038/s42003-021-02769-9
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation state of Mycobacterium tuberculosis impacts host immunity and augments pulmonary disease pathology

Abstract: In vitro phagocytosis of Mycobacterium tuberculosis (Mtb) aggregates (Mtb-AG), rather than similar numbers of single bacilli (Mtb-SC), induces host macrophage death and favors bacterial growth. Here, we examined whether aggregation contributes to enhanced Mtb pathogenicity in vivo in rabbit lungs. Rabbits were exposed to infectious aerosols containing mainly Mtb-AG or Mtb-SC. The lung bacterial load, systemic immune response, histology, and immune cell composition were investigated over time. Genome-wide trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Would the efficacy of VPM1002 also vary if compared to that of BCG Pasteur? Partly because of these questions, as well as recent reports showing biofilm-like structures in vivo 15 and increased virulence of aggregated Mtb in rabbits 17 , we have continued developing BCGΔBCG1419c, as we think that there could be populations that would be best protected with a different and novel TB vaccine candidate and that one potential replacement would not necessarily have universal application. Furthermore, the evaluation of a potential improved protection against biofilm-like structures produced in vivo afforded by BCGBCG1419c compared with BCG seems now more technically feasible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Would the efficacy of VPM1002 also vary if compared to that of BCG Pasteur? Partly because of these questions, as well as recent reports showing biofilm-like structures in vivo 15 and increased virulence of aggregated Mtb in rabbits 17 , we have continued developing BCGΔBCG1419c, as we think that there could be populations that would be best protected with a different and novel TB vaccine candidate and that one potential replacement would not necessarily have universal application. Furthermore, the evaluation of a potential improved protection against biofilm-like structures produced in vivo afforded by BCGBCG1419c compared with BCG seems now more technically feasible.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, last year, biofilm-like structures were reported in vivo in different animal models and human samples 15 , with our perspective on this finding already discussed 16 . Furthermore, it was just shown that aggregated Mtb increased lung pathology in rabbits 17 . We can now hypothesize that BCGΔBCG1419c might protect against these phenotypes (biofilm production and/or infection with aggregated Mtb) and therefore further develop this vaccine candidate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We found that so/sp and sp samples contained more clumps than 5µmF-prepared bacilli, but the clumps cannot account for the hyperinflammatory phenotype because when the sample was subsequently filtered (so/5uF), the aggregates were removed, but it was still hyperinflammatory. In addition, the literature describing the impact of aggregation on host interactions is difficult to interpret in light of our findings, as many of these studies used agitation with glass beads, filtration, sonication, or some combination of these procedures to generate the dispersed samples (Kolloli et al, 2021;Mahamed et al, 2017;Rodel et al, 2021). Thus, the aggregation of bacilli is likely an important virulence property of Mtb, which is overlooked in the effort to generate single cell suspensions.…”
Section: Discussionmentioning
confidence: 85%
“…[32][33][34][35] HDTs can support antimycobacterial host response at different stages: a) perturbating granuloma integrity to enhance drug penetration; b) modifying autophagy or phagosome maturation to increase intracellular killing; c) promoting cell-mediated response; d) inducing antimicrobial peptides and controlling inflammation response by avoiding tissue damage. 36 While the use of HDTs seem to support anti-TB treatment in symptomatic individuals, 37 no data nor anecdotal knowledge support the use of such therapies in people with asymptomatic or subclinical infection. 38 In other words, it is undeniable that some immunomodulatory treatments may alter the host-Mtb equilibrium, favoring either the host or the bacteria.…”
Section: Impact Of the Therapies Against Sars-cov-2 Onmentioning
confidence: 99%